2005
DOI: 10.1515/cclm.2005.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A protein levels as a possible aid in the diagnosis of acute appendicitis in children

Abstract: Hematological and biochemical tests, including white blood cell count (WBC), C-reactive protein (CRP) and other acute-phase reactants, have been used in the diagnosis of acute appendicitis. However, there is controversy among physicians about the value of this practice in children. The objective of our study was to evaluate serum amyloid A protein (SAA) levels in children with confirmed acute appendicitis and to compare the sensitivity and specificity of this marker of inflammation with those for WBC and CRP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Gronroos [4] reported that normal values of both WBCC and CRP were found in 7 of 100 consecutive children but in none of the 200 adults with pathologically confirmed acute appendicitis [7], and concluded that normal inflammatory markers can reliably exclude appendicitis in adults but not in children. Similarly, in a study by Lycopoulou et al [12] the sensitivity of elevated WBCC was 76%, and of elevated CRP only 62%, in 260 children with histologically confirmed appendicitis.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Gronroos [4] reported that normal values of both WBCC and CRP were found in 7 of 100 consecutive children but in none of the 200 adults with pathologically confirmed acute appendicitis [7], and concluded that normal inflammatory markers can reliably exclude appendicitis in adults but not in children. Similarly, in a study by Lycopoulou et al [12] the sensitivity of elevated WBCC was 76%, and of elevated CRP only 62%, in 260 children with histologically confirmed appendicitis.…”
Section: Discussionmentioning
confidence: 73%
“…The rationale of laboratory tests in the diagnosis of acute appendicitis is based on the possibility of detecting signs of systemic inflammation with a diagnostic tool that is widely available and easy to perform, is minimally invasive, has limited costs, and can be repeated if necessary [14]. Although, over the last few decades, several markers of inflammation have been proposed to increase diagnostic accuracy in acute appendicitis (including phospholipase A 2 [15], serum amyloid A, [12], leukocyte elastase [16], neutrophil count [9], and several interleukins and cytokines [6]), WBCC and CRP are certainly the most widely used. They can also provide complementary information, with WBCC rising in the early phases of the inflammatory response and CRP increasing in advanced appendicitis [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their specificity is low, because WBC or CRP levels tend to increase in all inflammatory diseases [1,2]. Several studies have explored the role of these biomarkers in improving the diagnosis of intra-abdominal inflammation in children and adults [3][4][5][6][7][8]. More accurate biomarkers are needed to reach the diagnosis for intra-abdominal inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%